A novel heterozygous HTRA1 mutation is associated with autosomal dominant hereditary cerebral small vessel disease. Issue 6 (2nd April 2020) - Zhuo, Zhong‐ling; Cong, Lu; Zhang, Jun; Zhao, Xiao‐tao
Abstract: Background: We investigated whether a heterozygous mutation that we newly identified in HTRA1 (high‐temperature requirement serine protease A1 gene) in a pedigree with autosomal dominant hereditary cerebral small vessel disease (SVD) reduces the function of HTRA1 and affects the transforming growth factor‐β1 (TGF‐β1)/Smad signaling. Methods: Whole‐exome sequence from the proband and her two sisters was examined using whole‐exome enrichment and sequencing. Expression of HTRA1 and TGF‐β1/Smad and HTRA1 activity were assayed using sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and western blotting analyses after transfecting wild‐type and mutant HTRA1 genes into HEK293 cells. Results: A new heterozygous mutation (c.614C>G:p.Ser205Cys) in HTRA1 was identified in the sequence encoding the trypsin‐like serine protease domain. The mutation was predicted to be deleterious by in silico tools. Moreover, in vitro activity and protein analyses revealed a loss‐of‐function effect of the mutation: the proteolytic activity of mutant HTRA1 was decreased, and, notably, this was accompanied by an increase in TGF‐β1/Smad protein levels. Conclusions: The heterozygous mutation HTRA1 S205C causing diminished protease activity is associated with—and could represent a cause of—autosomal dominant hereditary cerebral SVD. Our results also indicate a relationship between HTRA1 and TGF‐β1/Smad signaling. Abstract : The heterozygous mutation high‐temperature requirement serine protease A1 gene (HTRA1) S205C causing diminished protease activity is associated with—and could represent a cause of—autosomal dominant hereditary cerebral small vessel disease. Our results also indicate a relationship between HTRA1 and transforming growth factor‐β1/Smad signaling.